Love: there is (bio)chemistry between us - Manrique Muñante, Rubén (2013)
Romantic love involves biochemical processes in which substances such as neurotransmitters, neuromodulators and hormones interact with other nerve cells or organs. When being in love, dopamine levels increases, generating attention, desire and motivation in everything related to the beloved person. Serotonin, however, is present in low levels in this state. When the body does not supply the necessary amount of dopamine, oxytocin is released. Oxytocin is vital in long term relationships. Understanding the mechanism of oxytocin in humans is crucial not only for academic knowledge of the chemistry of love but also because it provides new lights for the treatment of some psychological disorders.